Participação democrática e cidadã como mecanismo de superação da crise ecológica no contexto jurídico brasileiro - Cristiane Velasque; Thiago Germano Álvares Da Silva; Wambert Gomes Di Lorenzo (Ius Humani. Jornal do direito, 2018)
This paper aims to investigate the importance of application the right to democratic and citizen participation in overcoming the ecological crisis. Democratic participation is a fundamental right of every citizen. Thus, the State has responsibility to make available instruments for its conscious and effective use. Brazil occupies the status of Democratic State of Right, according to the Federal Constitution, which provides for the possibility of direct and indirectly participation of the population. However, this exercise of citizenship often suffers limitations, without proper observance of the principles that make up participatory democracy. This limitation often occurs because of particular interests of certain economic groups, overriding environmental interests. It is important to be globally aware of the environmental crisis in the face of current problems, otherwise the natural resources will be depleted. It is of paramount importance the democratic participation in the environmental issue for the realization of the right to the ecologically balanced environment, which aims to provide a better quality of life. However, this study aims to investigate the limitations of mechanisms for democratic participation, since this compromises the legitimacy of decisions resulting from this participation, which is characterized by addictions. Therefore, it is not enough the legislative forecast, it is primordial the conscience of the humanity on the necessity of preservation of the natural resources, based on a universal environmental ethic. The present work uses the deductive method. And as a conclusion, it supports the importance of effectively applying this fundamental right in overcoming the ecological crisis.